Enantioseparation of 5,5′-Dibromo-2,2′-dichloro-3-selanyl-4,4′-bipyridines on Polysaccharide-Based Chiral Stationary Phases: Exploring Chalcogen Bonds in Liquid-Phase Chromatography - Paola Peluso; Alessandro Dessì; Roberto Dallocchio; Barbara Sechi; Carlo Gatti; Bezhan Chankvetadze; Victor Mamane; Robin Weiss; Patrick Pale; Emmanuel Aubert; Sergio Cossu (Molecules, 2021)
The chalcogen bond (ChB) is a noncovalent interaction based on electrophilic features of regions of electron charge density depletion (σ-holes) located on bound atoms of group VI. The σ-holes of sulfur and heavy chalcogen atoms (Se, Te) (donors) can interact through their positive electrostatic potential (V) with nucleophilic partners such as lone pairs, π-clouds, and anions (acceptors). In the last few years, promising applications of ChBs in catalysis, crystal engineering, molecular biology, and supramolecular chemistry have been reported. Recently, we explored the high-performance liquid chromatography (HPLC) enantioseparation of fluorinated 3-arylthio-4,4′-bipyridines containing sulfur atoms as ChB donors. Following this study, herein we describe the comparative enantioseparation of three 5,5′-dibromo-2,2′-dichloro-3-selanyl-4,4′-bipyridines on polysaccharide-based chiral stationary phases (CSPs) aiming to understand function and potentialities of selenium σ-holes in the enantiodiscrimination process. The impact of the chalcogen substituent on enantioseparation was explored by using sulfur and non-chalcogen derivatives as reference substances for comparison. Our investigation also focused on the function of the perfluorinated aromatic ring as a π-hole donor recognition site. Thermodynamic quantities associated with the enantioseparation were derived from van’t Hoff plots and local electron charge density of specific molecular regions of the interacting partners were inspected in terms of calculated V. On this basis, by correlating theoretical data and experimental results, the participation of ChBs and π-hole bonds in the enantiodiscrimination process was reasonably confirmed.